The aim of the research is to evaluate the effectiveness of micro fertigation system and application of cows fermented urine (uriferm) for chili (Capsicum annum sp.) Cultivation. The micro fertigation system with 0.5 mm inside diameter micro-tubing is used to control the flow from outlets along lateral. The lateral with 5/16 inch inside diameter is made of soft PVC hose. The result of the research showed that the micro fertigation system is running well. Randomized block design with four repl - Naswir .; Soedodo Hardjoamidjojo; Nora H. Pandjaitan; Hidayat Pawitan (Forum Pasca Sarjana, 2009)
The aim of the research is to evaluate the effectiveness of micro fertigation system and application of cows fermented urine (uriferm) for chili (Capsicum annum sp.) Cultivation.  The micro fertigation system with 0.5 mm inside diameter micro-tubing is used to control the flow from outlets along lateral.  The lateral with 5/16 inch inside diameter is made of soft PVC hose.  The result of the research showed that the micro fertigation system is running well. Randomized block design with four replications are used for the field experiment.  There are four treatments i.e. conventional culture by watering can (A), uriferm fertigation (B), non uriferm fertigation (C), and Hartus formula fertigation (D).  The laboratory analysis showed that the properties of uriferm increase in composition compared to non uriferm and used successfully as nutrition.  The micro fertigation system showed better result compared to the watering can on variable observation of plant and root development of chili.  The field experiments showed that the micro fertigation system significantly reduced volume of water used by 49.5% and raised chili yield by 61.2% compared to watering can.  The uriferm fertigation (B) showed better result compared to other treatments on wet weight of chili and water productivity.  The total income from 390 m2 irrigated land with micro fertigation system was about Rp 2,961,700,00/season and  feasible to apply with B/C ratio =  1.51, IRR value = 27.49% and NPV = Rp 387,413.83 at discount rate 9% per annum.   Key words: micro fertigation system, uriferm, chili, water productivity, small plots